Análise comparativa do composto de marketing das marcas Topshop, Melissa e Havaianas (ModaPalavra e-periódico, 2011)
The following study aims to study and present concepts related to marketing trough a search with three fashion brands considerate creative, they are: Topshop, Melissa and Havaianas. The marketing mix of the brands will be fragmented for a bigger understanding of the research, for then, to analyze at five tools used as a promotional way to the brands: flagship stores, products, campaigns, virtual platforms and creativity factor itself, which acts as a major tool of promotion. The analyses were always followed by analytical boards and images that represent in an illustrative way, the subject matter. At the end, it is presented considerations about the regarding analysis, emphasizing the importance of using creativity coupled with marketing strategies that provide a satisfactory experience for consumers and a differentiator for businesses.
Keywords: marketing; fashion; creativity